STUDY OF THE MELON DRYING PROCESS UNDER VARIOUS THERMAL TREATMENT CONDITIONS - Choriyev , Abdusattar (Journal of Research and Development, 2026)
The article presents the results of theoretical and experimental studies on the drying process of melon using infrared radiation. The specific features of heat and mass transfer during the dehydration of high-moisture cucurbit crops are examined, and existing methods for drying agricultural products are analyzed. The feasibility of applying infrared pre-treatment of raw materials in combination with infrared-convective drying is substantiated, as this approach intensifies the process and reduces its duration. It is established that exposure to infrared radiation promotes the opening of cellular structures and ensures uniform moisture removal throughout the entire volume of the material, making it possible to shorten the drying time by 1.5–2 times while maintaining the quality of the finished product. The obtained results can be used in the development of energy-efficient technologies and drying equipment for the processing of cucurbit crops.